EAD implementation process in the brazilian context: a look through pedagogy (Research, Society and Development, 2022)
Objective: to describe in the literature the process of implementing distance learning in the Brazilian context with a view through pedagogy. Method: This is a qualitative narrative review study, appropriate to discuss the state of the art of a given subject. The documents that composed it were retrieved through the Portal of Periodicals of Capes and ministerial documents that deal with the elapsed theme. Results: The history of distance learning in Brazil has always been linked to professional training, enabling people to perform certain activities or master certain skills, always motivated by commercial issues. The training of teachers regarding continuing and permanent education, historically in the Brazilian reality, was linked to distance education. Conclusion: With regard to pedagogy today it represents the largest course in students in this modality. It is believed that the pedagogy course is so widespread in this mold because it is an undergraduate degree that does not require large technological investments for its implementation and dissemination, as it is a cohesive profession with a vast area of ​​activity and with great possibility of absorbing the job market.